Mô hình cảnh báo sớm khủng hoảng tiền tệ: Nghiên cứu thực nghiệm tại Việt Nam - Vo Thi Thuy, Anh; Tran Nguyen Tram , Anh; Ha Xuan , Thuy (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
Based on the study of Kaminsky and Reinhart (1999), this paper studies and applies early warning systems of currency crisis to the case of Vietnam from 1996 to 2014. Its results show that the model signals the currency crisis six times during the observed period. Several principal indicators of the currency crisis in Vietnam include increased import, decreased export, excess real M1 balance, low international reserves and deposit growth, high interest rate and credit growth, high domestic-foreign rate differential, and decreased real output. Hence, the Government and the State Bank of Vietnam should grant apporiate policies not only to control the money supply and interest rate, but also to stimulate the ability of capital mobilization of Vietnam banking system and to facilitate export activities in the coming years.
Keywords: Currency; crisis; finance; early warning system